Histopathology Liver and Kidney of Tilapia (Oreochromis niloticus) that were infected with bacteria Streptococcus iniae - Etri Nopilita; Henni Syawal; Morina Riauwaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted from July to December 2015 in the Laboratory of Parasitic and Fish Diseases Faculty of Fisheries and Marine Sciences University of Riau. The purpose of this study was to determine the pathological changes of the liver and kidney of tilapia (O. niloticus) were infected with the bacterium S. iniae. The method used is an experimental method and histological structure of the fish will be analyzed descriptively. The treatments applied were intraperitoneal infection by S. iniae with different consentration, they were ; Kn (negative control, were not infected by S. iniae), P1 (infection by S. iniae with concentration 109 CFU/mL in a dose of 0,1 mL/fish), P2 (infection by S. iniae with concentration 107 CFU/mL in a dose of 0,1 mL/fish), P3 (infection by S. iniae with concentration 105 CFU/mL in a dose of 0,1 mL/fish), and than fisher were reared for 7 days. The results showed that the P1 kerusakn treatment of liver and kidney is more severe than the treatments P2 and P3, this was due to S. iniae able to damage or lysis of erythrocytes, neutrophils, and lymphocytes. In addition, this bacterium is septicemia so it can infect vital organs such as gills, liver, kidney, brain, and nervous system. Histopathologic liver tissue tilapia infected with the bacterium S. iniae indicate a hemorrhage, necrosis, congestion and degenerative. Histopathological kidney tissue tilapia infected with the bacterium S. iniae showed abnormality characterized by the occurrence of hemorrhage, necrosis, congestion and degenerative.   Key words : Oreochromis niloticus, Streptococcus iniae, Histopathology, Liver, Kidney